2017
DOI: 10.1002/2211-5463.12180
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ by baicalin attenuates pulmonary hypertension in an infant rat model by suppressing HMGB1/RAGE signaling

Abstract: Pulmonary hypertension (PH) is a vascular disease, and proinflammatory factors are strongly implicated in its pathogenesis, causing right ventricular (RV) hypertrophy and heart failure. Baicalin exhibits potent anti‐inflammation activity. This study aimed to investigate the curative effects of baicalin in an infant rodent model of PH and to further explore the underlying mechanisms. A PH model in infant rats was induced by hypoxia and the resulting rats were administered baicalin in incremental dosages. Invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…These changes seem to highlight a metabolic orientation skewing towrads oxidative metabolism. The cellular response and association between high mobility group protein B1 (HMGB1) (P09429), (TGF)-β1 [28] and peroxisome proliferator-activated receptor (PPAR)-γ [29] occur in an environment (P63151, P0CG48, Q9Y263) dominated by TLR4 signaling towards downstream MyD88/TRIF signaling [30]. However, these biological responses do not appear to mediate mitochondrial dysfunction (O95831-3, P08758, P39656 and P04843) as LPS does.…”
Section: Phenotypic Changesmentioning
confidence: 99%
“…These changes seem to highlight a metabolic orientation skewing towrads oxidative metabolism. The cellular response and association between high mobility group protein B1 (HMGB1) (P09429), (TGF)-β1 [28] and peroxisome proliferator-activated receptor (PPAR)-γ [29] occur in an environment (P63151, P0CG48, Q9Y263) dominated by TLR4 signaling towards downstream MyD88/TRIF signaling [30]. However, these biological responses do not appear to mediate mitochondrial dysfunction (O95831-3, P08758, P39656 and P04843) as LPS does.…”
Section: Phenotypic Changesmentioning
confidence: 99%
“…It was observed that after oral administration in the doses from 10 mg/kg/day to 30 mg/kg/day baicalin significantly attenuated pulmonary arterial pressure, and right ventricular hypertrophy in infant rats. Few biomarkers such as advanced glycation end products, IL 6, TGFβ1 in bronchoalveolar lavage fluid (BALF) were also reduced after baicalin treatment [53]. Furthermore, in this study it was shown that HMGB1/RAGE signaling can be taken into account as a molecular point of action for baicalin.…”
Section: In Vivo Studies Related To the Various Models Of Hypertensionmentioning
confidence: 58%
“…Baicalin has been widely studied in several in vitro and in vivo models and showed many activities such as: anti-viral [42], anti-oxidative via several pathways [43], neuroprotective and enhancin cognitive functions [44,45], anti-inflammatory [46], anti-cancer [47,48], and hepatoprotection [49]. In recent years, many studies showed anti-hypertensive properties of baicalin [46,[50][51][52][53][54][55][56][57][58][59][60], and also cardioprotective [50], antiplatelet, anticoagulant, and profibrinolytic activities [61].…”
Section: Influence In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations